Peningkatan Kualitas Pelayanan Perpustakaan UINSU Melalui Kerjasama Antar Perpustakaan - Elgy Wijayanti; Sarida Sinulingga; Yusniah Yusniah (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article explains how to improve the quality of university libraries through collaboration between libraries. The quality of the library can be interpreted as an achievement that is carried out through a series of processes, both in short and long term activities. The process of creating a series of quality libraries can be specified in three ways, namely paying attention to the quality of input, process and context quality and quality of results. Viewed as a means of input quality achievement has mental preparation, service processes are supported and adapted to user needs so that in the end it can produce results as the previous product series. The library is one of the information provider institutions. For this reason, the library must be able to provide the information needed by its users. To maintain and increase user satisfaction with library services, various things can be attempted, including establishing cooperation with the library. With this collaboration, it is possible for users to be able to access information owned by other libraries and sources of information outside their library. This collaboration will complement each other and better meet the information needs of its users. Keywords: library; service; collaboration between libraries